Entrepreneurial ecosystem knowledge spillover in the face of institutional voids: groups, issues, and actions. Issue 1 (2nd January 2021) - Bendickson, Josh S.; Irwin, Jennifer G.; Cowden, Birton J.; McDowell, William Cordell
ABSTRACT: The presence or absence of formal institutions impacts entrepreneurship potential and influences the paths of entrepreneurial ventures. When institutions are lacking or weak, institutional voids may be present. Knowledge spillover can mitigate problems caused by institutional voids by substituting for such voids or through sharing information about navigating these environments. We study the associated impacts on entrepreneurs and entrepreneurship ecosystems and how knowledge spillover is valuable within entrepreneurial ecosystems with institutional voids. Non-institutional drivers of entrepreneurship and examples of specific actions that are taken to stimulate entrepreneurship are also explored as a means of better understanding entrepreneurship activity within weak or failing institutions. To assess knowledge spillover in an entrepreneurial ecosystem with institutional voids, the U.S. city of Detroit, Michigan was selected and a content analysis was conducted using news articles related to "Detroit" and "entrepreneurship" from 2006–2018. The findings present valuable insights for cities or regions facing similar situations.